Implikasi Pendidikan Multikultural Terhadap Pola Pikir Keagamaan Generasi Milenial - Sakhat Maulidah; Nurul Qomariyah; Siti Antika Ririn Pratiwi (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
This article reviews the Implications of Multicultural Education on the Religious Mindset of the Millennial Generation. This article aims to explain the impact of implementing multicultural education on the religious mindset of the millennial generation. The writing of this article uses a type of qualitative research with library research methods. The results of this study are to determine the impact of the implementation of multicultural education on the religious mindset of the millennial generation, namely: (1) improving self understanding and self-concept well. (2) increase sensitivity in understanding other people. (3) respecting religious and cultural differences between groups regarding an event, values, and behavior. (4) open our minds in responding to various issues. (5) Stay away from stereotypical views and try to respect others. With multicultural education, a person will become a good human being and more tolerant of diversity, and not passionate about the religion he adheres to. Therefore, a religious mindset based on multicultural education needs to be instilled as early as possible. This includes an appreciation of the existence of cultural plurality, recognition of human dignity and rights, and development of human responsibility towards the inhabited earth.